1992
DOI: 10.1007/bf02780555
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational modifications of nerve cytoskeletal proteins in experimental diabetes

Abstract: Axonal transport is known to be impaired in peripheral nerve of experimentally diabetic rats. As axonal transport is dependent on the integrity of the neuronal cytoskeleton, we have studied the way in which rat brain and nerve cytoskeletal proteins are altered in experimental diabetes. Rats were made diabetic by injection of streptozotocin (STZ). Up to six weeks later, sciatic nerves, spinal cords, and brains were removed and used to prepare neurofilaments, microtubules, and a crude preparation of cytoskeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 63 publications
2
24
1
Order By: Relevance
“…Nearly a decade ago, it was suggested that carbonyl-derived post-translational modifications of neurofilaments may account for the biochemical properties of neurofibrillary tangles, possibly as a result of extensive cross-links (22,39). Because of their relatively long half-life, cytoskeletal proteins are preferred reactants with reactive carbonyl compounds, such as lipid peroxidation products or glucose (40,41). A first attempt to induce Tau glycation in vitro was made by short term incubation with glucose, but this did not result in the formation of PHFs (42).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly a decade ago, it was suggested that carbonyl-derived post-translational modifications of neurofilaments may account for the biochemical properties of neurofibrillary tangles, possibly as a result of extensive cross-links (22,39). Because of their relatively long half-life, cytoskeletal proteins are preferred reactants with reactive carbonyl compounds, such as lipid peroxidation products or glucose (40,41). A first attempt to induce Tau glycation in vitro was made by short term incubation with glucose, but this did not result in the formation of PHFs (42).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, metabolically and genetically driven autophagy deficiency was associated with dysfunctional lysosomes accumulated in podocytes. The preservation of lysosome-and autophagy-mediated proteostasis may be critical for podocytes to cope with increased amounts of damaged proteins produced during diabetes, a condition favoring increased intensity of nonenzymatic modifications of amino acids (32) and high incidence of posttranslational modifications of proteins as reported in b-cells and nerves (33,34).…”
mentioning
confidence: 99%
“…Pathological, post-translational changes of neurofilament structure, such as extensive phosphorylation [46][47][48] and nonenzymatic glycation 46,49,50 have also been shown to affect neurofilament transport, resulting in neurofilament accumulation and consequently altering axonal structure and function leading to nerve degeneration. Recent experiments focused on axonal transport impairment in the diabetic peripheral nerve revealed that neurofilament transport is indeed delayed and this delay coincides with the increased level of Carboxymethyllysine (CML), an advanced glycation end-product (AGE) indicative of high levels of glycation likely affecting neurofilament structure 19 .…”
mentioning
confidence: 99%